Sistem Digitalisasi Data Pasien Klinik Bhakti Medika Dengan Image Processing Ocr (Optical Character Recognition) Menggunakan Tesseract - Siti Maesaroh; Iqbal Alannurrochman (Teknik Informatika Fakultas Ilmu Komputer, 2025)
Patient data digitization has become a crucial need to improve the efficiency and accuracy of information management in healthcare facilities. The aim of this study was to design and implement a patient data digitization system at the Bhakti Medika Clinic using the CodeIgniter web framework, MySQL database, and Tesseract-based OCR technology. This system is designed to allow users to upload medical document images through a web interface, extract text automatically using Tesseract, and store the results in a structured database. The methods used in this study include observation, interviews, documentation, and system testing using a black box approach. The results show that the system successfully improves data processing efficiency, accelerates information access, and reduces manual input errors. The use of Tesseract OCR has proven effective in extracting information from high-quality images, with validation conducted using a Confusion Matrix to measure the accuracy of the extraction results.